2020
DOI: 10.1002/cti2.1207
|View full text |Cite
|
Sign up to set email alerts
|

Autologous non‐human primate model for safety assessment of piggyBac transposon‐mediated chimeric antigen receptor T cells on granulocyte–macrophage colony‐stimulating factor receptor

Abstract: Objectives Chimeric antigen receptor (CAR)‐T cell therapy redirected to specific antigens on tumor cells is a promising immunotherapy strategy for various cancers. Most target antigens are also expressed on normal tissues at varying levels, and therefore, a considerable challenge in the field is determining safety profiles, including life‐threatening off‐tumor and off‐target toxicities. The granulocyte–macrophage colony‐stimulating factor receptor (hGMR) is a promising target for CAR T‐cell therapy for a subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…SB pioneered applications with the well-characterized CD19-specific CAR-T cells (reviewed in [ 24 , 206 ]), and was joined by PB [ 206 , 207 , 208 ] and Tol2 [ 113 ] to demonstrate suppression of B cell lymphoma progression both in vitro and in vivo. The most recent developments include CAR-T cell engineering for alternative targets such as the granulocyte-macrophage colony-stimulating factor receptor (hGMR or CD116) for hematological malignancies [ 209 ], the epidermal growth factor receptor (EGFR) as a target for non-small-cell lung carcinoma [ 210 ], glypican-3 and EGFRvIII targeting hepatocellular carcinoma [ 211 , 212 ] and membrane-proximal mesothelin (MSLN) epitope-targeting against MSLN-positive solid tumors [ 213 ]. Additionally, SB and PB have been used to generate allogenic “off-the-shelf” CAR-natural killer (NK) cells that have shown encouraging results against solid tumors [ 214 , 215 ].…”
Section: Preclinical Applicationsmentioning
confidence: 99%
“…SB pioneered applications with the well-characterized CD19-specific CAR-T cells (reviewed in [ 24 , 206 ]), and was joined by PB [ 206 , 207 , 208 ] and Tol2 [ 113 ] to demonstrate suppression of B cell lymphoma progression both in vitro and in vivo. The most recent developments include CAR-T cell engineering for alternative targets such as the granulocyte-macrophage colony-stimulating factor receptor (hGMR or CD116) for hematological malignancies [ 209 ], the epidermal growth factor receptor (EGFR) as a target for non-small-cell lung carcinoma [ 210 ], glypican-3 and EGFRvIII targeting hepatocellular carcinoma [ 211 , 212 ] and membrane-proximal mesothelin (MSLN) epitope-targeting against MSLN-positive solid tumors [ 213 ]. Additionally, SB and PB have been used to generate allogenic “off-the-shelf” CAR-natural killer (NK) cells that have shown encouraging results against solid tumors [ 214 , 215 ].…”
Section: Preclinical Applicationsmentioning
confidence: 99%
“… 36 To verify the safety of CAR-T products, we have previously established non-human primate (NHP) models to better recapitulate human physiology using lymphodepleted cynomolgus macaques ( Macaca fascicularis ). 37 , 38 …”
Section: Resultsmentioning
confidence: 99%
“…6 Total white blood cell and lymphocyte counts were suppressed below their normal limits in all groups according to the in‐house reference data (Supplementary table 1) in all macaques on day −1 (Figure 1b) and persisted throughout the investigation (Figure 2a) without the occurrence of any overt infections. In contrast, the numbers of neutrophils, monocytes and platelets, as well as haemoglobin levels, were mostly within normal limits, 5 and the number of reticulocytes increased after day 4 (Figure 2a). These data indicated that the conditioning by FDR/CPA was specific to the reduction in the lymphocyte count and that the suppressive effect on bone marrow function might be transient.…”
Section: Resultsmentioning
confidence: 93%
“…Since an immunodeficient mouse model would not be suitable for assessing immunological on‐target/off‐target toxicity because of the substantial interspecies divergence between rodents and humans, a non‐human primate (NHP) model has been utilised as an alternative for the safety assessment of T‐cell products 4 . To evaluate on‐target/off‐target toxicity in an NHP model, the CAR molecule should be introduced into NHP T cells; however, a limitation of this approach would be the differences in the quality of NHP and human CAR‐T cells, as NHP CAR‐T cells cannot completely mimic the properties of the final human CAR‐T cell product used in clinical trials 5 …”
Section: Introductionmentioning
confidence: 99%